Diplomatic Protection Efforts of the Consulate General of the Republic of Indonesia in Johor Bahru for Indonesian Migrant Workers as the Domestic Helpers (PLRT) in 2018-2019 - Firnanda Haumahu, Jessica; H.J. De Fretes, Christian; Romulo Simanjuntak, Triesanto (PT ARRUS Intelektual Indonesia, 2023)
The limitations of a country in providing employment opportunities for its citizens encourage migration activities to other countries. Citizens who migrate for work generally have the same expectations, which are to improve living standards and meet their needs. However, practically, labor migration also brings risks and challenges, particularly for Indonesian Migrant Workers as Domestic Helpers (PMI PLRT) who can be categorized as a vulnerable group. PMI PLRT is often faced with various problems, such as unfair treatment, acts of violence, exploitation, and violations of rights committed by employers. This research focuses on the diplomatic protection efforts of the Indonesian Consulate General in Johor Bahru as one of the representatives of the Republic of Indonesia in Malaysia, for PMI PLRTs in their accredited areas of Negeri Johor, Melaka, Negeri Sembilan, and Pahang during 2018-2019. This research was conducted using a qualitative descriptive method and a diplomatic protection approach in the form of the perspective of international law. The results of the study show that the Indonesian Consulate General in Johor Bahru provides diplomatic protection to PMI PLRT by integrating two safeguards namely, preventive efforts, such as disseminating information to stakeholders in Indonesia, creating and informing work contracts, strengthening cooperation with Malaysian authorities, as well as repressive efforts by identifying problems in receiving PMI PLRT complaints, contacting relevant parties, providing shelters, facilitating the repatriation of PMI PLRT to Indonesia. The two diplomatic protection efforts that have been carried out by the Indonesian Consulate General in Johor Bahru are expected to provide a fairer and safer working environment for PMI PLRT